Analisa Rekayasa Ulang Proses Bisnis Pada UD. Top Stiker - Dewi Aprilitasari; Ilyas Nuryasin; Vinna Rahmayanti (Jurnal Repositor, 2020)
Re-engineering is used to identify, analyze, and redesign the core business processes of the company/organization aimed at achieving a dramatic increase in critical performance measurements such as cost, quality, service, and speed. The achievement of re-engineering is to support more a corporate mission and reduce costs. UD. Top Stiker is one of the companies engaged in the field of mobile phone accessories, stationery and offices and motorcycles are currently developing, so the need to improve the quality of service is getting better. But the business process in UD. Top Stiker has not been going well and has problems that can interfere with the running of operational activities UD. Top Stiker. Using the BPR method and SWOT analysis to generate alternative strategies and BPMN for business process modeling. The research used to obtain data was obtained through literature studies, observations, interviews and provided questionnaires to UD. Top Stiker owners. The final result of this study was a recommendation of a business process redesign by reducing several process stages from the 18 process stages to 13 process stages so that it become more fast and simple. While the value of the IFAS strength factor is 1.55 and the weakness factor is 1.75, while the value of the EFAS opportunity factor is 1.7 and the risk factor is 1.45.